Um estado da arte das pesquisas acadêmicas sobre modelagem em educação matemática (de 1979 a 2015) nas áreas de Educação e de Ensino da Capes: as dimensões fundamentadas e as direções históricas - Soares, Maria Rosana (2017)
The aim of this thesis was to develop, analyze and emphasize the well-founded dimensions and historical directions of academic research on mathematics modeling in mathematics education (from 1979 to 2015) in the Education and Teaching Areas of Capes (2016), starting with the elaboration, discovery and revelation of a creative process of scientific investigation for the realization of a state of the art of research. In order to do so, it is concretized through the construction and intervention in the said creative process, organized in phases, which involves two distinct and related moments in the state of the art. The first step was to address the well-founded dimensions and historical directions regarding the sources, origins, productions and transformations of these research pieces (up to 2015) in the said areas, being carried out through three phases – choice of a theme, formulation of the problem and collection, recording, organization, preparation and coding of data. The second stage concerns the introduction, development and consolidation of this approach (from 1979 to 2015) by means of the last proposed phase: results, discussion and report of the problem with respect to the analysis, interpretation, description and disclosure of data. Methodologically, the research strategies covered in the state of the art were developed from a qualitative approach, its characteristics and requirements. More specifically, we used descriptive and analytical strategies based on data collection and recording procedures, using public documents, dissertations and theses, as well as general means and audiovisual material: physical and online communications, libraries, telephone and / or e-mail seeking samples, and software: Microsoft Office Excel and Microsoft Office Word. Therefore, the investigation addressed the source of the data collected, the indirect documentation and the materials available in the scientific domain, as well as to the bibliographic research, addressing bibliographic data sources in line with the type of publication. For the accomplishment of this creative process, another qualitative strategy was used according to its procedures of codification, analysis and interpretation of the collected data, based on a theory founded, interpreted and constructed from them. The grounded dimensions revealed the conceptual and subjective elements and the theoretical constructs that emerged, sustaining and meaning the modeling theme to the development, analysis and disclosure of the state of the art, deriving from a relevant creative process of research founded on the data based on a natural environment, where the researcher is a key instrument, who uses multiple methods, complex reasoning through the inductive and deductive logic, document meanings, emergent project, interpretation and holistic report. Historical directions revealed the institutions, programs, courses, regions, and guidance that leveraged the introduction, development and consolidation of modeling research (from 1979 to 2015): Education Area – 45 (17.24%) MA and 10 (3.83%) DO in Education programs (UNICAMP, FURB, UEPG) and Teaching Area – 101 (38.70%) MA, 37 (10.34%) DO and 78 (29.89%) MP in Mathematics Education programs, Science Teaching and Mathematics Education and Education in Science and Mathematics (UNESP/RC, UEL, UFPA and PUC/SP), 71 (27.20%) running in São Paulo, 49 (18.77%) in Paraná, 47 (18.01%) in Rio Grande do Sul, 27 (10.34%) in Minas Gerais and 21 (8.05%) in the Southern and Southeastern regions – Santa Catarina and Pará. The main precursors of modeling which were considered were D’Ambrosio, Barreto and Bassanezi, and also their essential successors, Almeida, Santo and Biembengut, who contributed to the maturity of this teaching strategy for mathematics learning in the research pieces of the two Capes areas that were investigated